UNBOXING A HIDDEN AGENDA OF THE WORLD’S WESTERNISATION; A NARRATIVE LITERATURE REVIEW OF THE HISTORY OF DEVELOPMENT THEORY - Hamdy, M. Kholis (EMPATI: Jurnal Ilmu Kesejahteraan Sosial, 2020)
Abstrak. To say “No” to development, by means of westernisation, in the current context may be irrelevant, especially when the definition is not proportionally set in place. Power dynamics and shifting between the North and the South or the West and The East become vivid where world polarisation is a no longer absolute measurement in socio, economic, and politics. There is no clear division on the binary. This article serves a purpose of a historical recollection of how the term development by means of westernisation by modernizing the entire world through ‘development agenda setting’ with long globalized westernisation efforts have a significant impact on the world’s inequality. By reviewing articles narratively on the reference of development theory history, the vision of distributing equal benefits in the current world setting may not fall into similar past development agenda and development mainstreaming. Thus development ought to evolve from western origins to a global faith initiative to shape the world into non-interference, equality, and mutual benefit of sustainable development for each individual. This article concludes that the history of development theory has demonstrated the hidden agenda of the westernisation of the world since the beginning of development project, namely from the transitional period of the late nineteenth century to the beginning twentieth century. The remark of Truman is truly considered as the formal embarkation of the new era of the bold program so-called development project. Abstrak. Menolak pembangunan, dalam pengertiannya westernisasi, pada konteks masa kini tidaklah relevan, khususnya ketika definisi pembangunan tidak didudukkan pada tempatnya secara proporsional. Dinamika kekuasaan dan peralihan antara Utara dan Selatan atau Barat dan Timur semakin jelas dimana polarisasi dunia tidak lagi menjadi ukuran yang absolut dalam ranah sosial, ekonomi dan politik. Tidak ada pembagian yang jelas antara dua bagian tersebut. Artikel ini bertujuan sebagai suatu penghimpunan ulang historis tentang bagaimana istilah pembangunan dalam pengertiannya westernisasi dengan memodernisasi seluruh dunia melalui ‘pengaturan agenda pembangunan’ dengan upaya-upaya westernisasi global yang panjang memberi dampak signifikan terhadap ketimpangan dunia. Dengan meninjau beberapa artikel secara naratif yang menjadi referensi sejarah teori pembangunan, visi untuk mendistribusikan manfaat-manfaat yang sama dalam pengaturan dunia saat ini kiranya tidak terjebak pada agenda pembangunan masa lalu yang serupa dan pengarusutamaan pembangunan. Dengan demikian pembangunan harus berubah perlahan dari asal muasal Barat-nya kepada inisiatif keyakinan global untuk menajamkan dunia menuju pembangunan yang berkelanjutan yang non-intervensi, setara, dan saling bermanfaat bagi setiap individu. Artikel ini menyimpulkan bahwa sejarah teori pembangunan telah memperlihatkan agenda terselubung dari westernisasi dunia sejak awal proyek pembangunan, yaitu dari periode transisi pada akhir abad ke-19 hingga awal abad ke-20. Kesimpulan Truman sangat dipertimbangkan sebagai embarkasi formal era baru program yang disebut proyek pembangunan.